Analisis Kemampuan Microteaching Mahasiswa Pendidikan Bahasa Arab Universitas Muhammadiyah Makassar - Abd. Rahman; Fatmawati Fatmawati; Abdul Jabbar Tahir (Jurnal Ilmiah Wahana Pendidikan, 2023)
Microteaching is a compulsory subject for students of the Arabic Language Education Study Program. As prospective teachers, students are required to be able to teach and practice a good classroom management system. Being able to apply basic teaching skills is something that must be mastered and developed by students in doing microteaching. The purpose of this study was to analyze the basic teaching skills of students through microteaching students of the Arabic Language Education Study Program Semester VI for the 2021/2022 academic year. This study uses a qualitative descriptive research method. From this analysis it can be concluded that students' microteaching abilities are greatly influenced by students' teaching preparation through making lesson plans, the more measurable class management through lesson plans made by students shows better teaching abilities resulting in student microteaching scores with an average score of 84.